Sheikh Muhammad Metwally Al Shaarawy his life and interpretation: A search extracted for a chapter of the thesis that has not yet been discussed for the purpose of discussion - Darwish, Maher; Suleiman, Naseer (Humanities Journal of University of Zakho, 2021)
Sheikh Muhammad Metwally Al Shaarawy is considered one of the prominent contemporary interpreters who served the Islamic nation with his sciences, and his lineage extends to the people of the Prophet’s House; And because his environment in which he lived was characterized by righteousness and piety, and because his father encouraged him to learn religious sciences, Sheikh Al Shaarawy became one of the leading scholars. After scholars and professors, the Sheikh accomplished a unique interpretation of its kind and called it (Al-Khawatir) He aimed primarily at education and reform, and he is the author of the first oral interpretation, and his interpretation was characterized by ease and simplicity, a clear phrase understood by the common people and the private, it has been copied like a folder for fourteen times، and He followed his fielders according to the order of the Qur’an, and its interpretation is still broadcast through various media.